TARHANDS: A MESSY MANIFESTO - Cariou, Warren (Imaginations: Journal of Cross-Cultural Image Studies, 2012)
This essay attempts to make visible the physical reality of the Athabasca oil sands mining developments in Canada, a reality that has been occluded by corporate and governmental disinformation as well as by citizens’ unwillingness to face the consequences of their actions and their inaction. By presenting photographs of oil sands mining operations interspersed with brief ironic narratives, aphorisms and poems, the essay creates a collage of disjunctive responses to the contemporary situation in the Canadian petro-state. Given that this situation is one of national self-deception, denial and fundamentally irrational behavior, the paper sets aside any attempt to make reasoned arguments about conservation or regulation, and instead embraces irrationality as the last possible mode of engagement with a contemporary public that will no longer listen to reason. In tone and structure the essay echoes F. T. Marinetti’s 1909 “Futurist Manifesto,” but it is very different in its intent, mapping a way toward a different kind of future than the technologized and hyper-individualistic one that Marinetti espoused. By moving into the realm of the irrational and engaging with Canadian petroculture as an expression of a kind of national unconscious, the essay attempts to reveal some of the psychological structures that prevent Canadians from seeing the dirt that is on their hands.